Fueling the future: Emission characteristics and sustainability of high-octane gasoline biofuels derived from lignocellulosic biomass - Tamer M.M. Abdellatief; Mohamed Koraiem M. Handawy; Amr Kamel; Hamada Mohamed Abdelmotalib; Ahmad Mustafa; Farrukh Jamil; Xiongbo Duan; Tareq Salameh; Abdul-Kadir Hamid; Mousa Hussein (Results in Engineering)
The current study demonstrates a safe and effective approach for generating gasoline biofuels RON 98 and RON 92 using light straight-run naphtha, isomerate, and reformate as base components. These biofuels are based on isopropyl alcohol, which has strong anti-detonation qualities. The impact of isopropanol as a clean, renewable, sustainable, and environmentally beneficial additive on the gasoline pool was demonstrated by analyzing the physical and chemical characteristics of the generated blends. Commercial gasoline with a rating of 92 octane and gasoline biofuel with ratings of 98 and 92 octane were compared using the exhaust emissions properties, which include carbon monoxide (CO), unburned hydrocarbons (HC), carbon dioxide (CO2), nitrogen oxides (NOX), and oxygen (O2). Engine speeds at which the analysis emissions were conducted were 1000, 1950, and 2650 rpm, respectively. The results of the experiment demonstrated an improvement in both the quantity and light naphtha grade. The findings reported that gasoline biofuels, particularly the 98 RON blend, reduced HC and CO emissions compared to commercial gasoline, with more significant improvements at higher engine speeds. Moreover, gasoline biofuel RON 98 showed superior fuel efficiency with the lowest specific fuel consumption and CO₂ emissions across all engine speeds. The produced gasoline biofuel 98 RON demonstrated the lowest CO emissions, with a marked drop from 1.99 % at 1000 rpm to 0.65 % at 2650 rpm. Lastly, 98 RON gasoline biofuel exhibited the highest air velocity at higher engine speeds, indicating potential improvements in engine performance under those conditions. These results suggest that gasoline biofuel RON 98 could be a cleaner and more efficient alternative to traditional gasoline, particularly in high-performance engine applications.